Frequency and phenotypic spectrum of germline mutations in POLE and seven other polymerase genes in 266 patients with colorectal adenomas and carcinomas. Issue 2 (20th January 2015) - Spier, Isabel; Holzapfel, Stefanie; Altmüller, Janine; Zhao, Bixiao; Horpaopan, Sukanya; Vogt, Stefanie; Chen, Sophia; Morak, Monika; Raeder, Susanne; Kayser, Katrin; Stienen, Dietlinde; Adam, Ronja; et al.
<x xml:space="preserve">Abstract</x> In a number of families with colorectal adenomatous polyposis or suspected Lynch syndrome/HNPCC, no germline alteration in the APC, MUTYH, or mismatch repair (MMR) genes are found. Missense mutations in the polymerase genes POLE and POLD1 have recently been identified as rare cause of multiple colorectal adenomas and carcinomas, a condition termed polymerase proofreading‐associated polyposis (PPAP). The aim of the present study was to evaluate the clinical relevance and phenotypic spectrum of polymerase germline mutations. Therefore, targeted sequencing of the polymerase genes POLD1, POLD2, POLD3, POLD4, POLE, POLE2, POLE3 and POLE4 was performed in 266 unrelated patients with polyposis or fulfilled Amsterdam criteria. The POLE mutation c.1270C>G;p.Leu424Val was detected in four unrelated patients. The mutation was present in 1.5% (4/266) of all patients, 4% (3/77) of all familial cases and 7% (2/30) of familial polyposis cases. The colorectal phenotype in 14 affected individuals ranged from typical adenomatous polyposis to a HNPCC phenotype, with high intrafamilial variability. Multiple colorectal carcinomas and duodenal adenomas were common, and one case of duodenal carcinoma was reported. Additionally, various extraintestinal lesions were evident. Nine further putative pathogenic variants were identified. The most promising was c.1306C>T;p.Pro436Ser in POLE. In conclusion, a PPAP was identified in a substantial number of polyposis and familial colorectal cancer patients. Screening for polymerase proofreading mutations should therefore be considered, particularly in unexplained familial cases. The present study broadens the phenotypic spectrum of PPAP to duodenal adenomas and carcinomas, and identified novel, potentially pathogenic variants in four polymerase genes.